Acoustic behaviour of two large terrestrial mammals in relation to resources maintenance and mating systems: wolf(Canis lupus) and red deer (Cervus elaphus) as model species - APOLLONIO, Marco (Università degli studi di Sassari, 2013)
The high variability of vocalization is due to their function, the habitat where they evolved and the physical constraints of the emitters. The aim of this study were to analyse the acoustic behaviour of two large terrestrial mammals, wolf (Canis lupus) and red deer (Cervus elaphus), in relation to resources maintenance and mating systems.Firstly, I analysed the Italian wolf howl. I found two forms of howl; both types are uttered within the lowest frequencies of the wolf’s vocal range, confirming the acoustic adaptation hypothesis, and thus, that low frequencies are more useful for long distance communication. Moreover, I found a group vocal signature into the packs. This characteristic is constant both within biological season and between two consecutive years.Secondly, I analysed the red deer mating calls. I described the vocal repertoire of Iberian red deer (C. e. hispanicus) males and I quantified variation of the roar of three free ranging subspecies. Iberian red deer repertoire consists of four call types and presents the “short common roar”, absent in the repertoire of the others subspecies. Among red deer subspecies exists a strong vocal divergence:C.e. hippelaphuspresent the highest intra population variability, followed byC. e. corsicanusandC. e. hispanicus. Between subspecies, the highest bioacoustic differences were found betweenC. e. hispanicusandC. e. corsicanuswhile this last population andC.e. hippelaphusare the most related subspecies.